A partial mediation effect of father-child attachment and self-esteem between parental marital conflict and subsequent features of internet gaming disorder in children: a 12-month follow-up study - Hyunsuk Jeong; Hyeon Woo Yim; Seung-Yup Lee; Hae Kook Lee; Marc N. Potenza; Sun-Jin Jo; Hye Jung Son (BMC, 2020)
Abstract Background This study evaluated whether parent-child attachment and self-esteem may mediate the relationship between parental marital conflict and increases in features of internet gaming disorder (IGD) in children at 1 year. Methods The baseline and one-year follow-up data for 268 pre-teens aged between 9 and 10 from the Internet User Cohort for Unbiased Recognition of Gaming Disorder in Early Adolescence (iCURE) study were collected. The students were children at low risk for IGD in the initial self-reported assessment, anyone living with both parents, current game user at baseline, and those who completed a 12-month follow-up assessment. The Internet Game Use-Elicited Symptom Screen (IGUESS) was used to identify increases in IGD features at 12 months. To examine a potential mediation effect, structural equation modeling was performed. Results The direct effect was statistically significant, and parental marital conflict at baseline significantly predicted the increases in IGD features in children at the 12-month follow-up after adjusting for gender, sex, socioeconomic status, and baseline IGUESS score (ß = 0.206, P = 0.003). The indirect effect showed that attachment to fathers through self-esteem was a significant mediating effect (ß = 0.078, P = 0.045). Parental marital conflicts were associated with increases in IGD features in children through poor father-child attachment, and in turn, the lower levels of self-esteem in the children. Conclusions Parents, especially fathers, should make an effort to bond with their children to reduce the risk of their children's developing the IGD features.